Pelatihan Membangun Website CRUD Dengan Pemrograman PHP Pada Siswa/I SMK Swasta Free Methodist Medan - Fahmi Ruziq; Subhan Hafiz Nanda Ginting; M. Rhifky Wayahdi (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Education has become the primary foundation for the young generation in the digital age. Through dedication to society, a positive contribution to the world of education can be realized. Although IT graduates are on the rise, most are not yet in line with industry standards. The development of soft skills has become crucial in producing successful graduates. Web development remains in demand, however, the gap between education and labour market demand needs to be overcome. This paper deals with "PHP CRUD Website Training for Private SMK Free Methodist Field Students" to enhance students' knowledge and skills. Participants are invited to understand the concepts of web development with PHP and career potential in the IT industry. This training has a positive impact on improving the knowledge and skills of students in web development as well as giving an overview of the potential career opportunities in the ICT industry.